2016
DOI: 10.5194/bg-13-3607-2016
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for submicron characterization the carbon binding of reactive minerals in long-term contrasting fertilized soils: implications for soil carbon storage

Abstract: Mineral binding is a major mechanism for soil carbon (C) stabilization. However, the submicron information about the in situ mechanisms of different fertilization practices affecting organo-mineral complexes and associated C preservation remains unclear. Here, we applied nano-scale secondary ion mass spectrometry (NanoSIMS), X-ray photoelectron spectroscopy (XPS), and X-ray absorption fine structure spectroscopy (XAFS) to examine differentiating effects of inorganic versus organic fertilization on interactions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 50 publications
4
22
0
Order By: Relevance
“…al., 2017). Secondary Fe-minerals (e.g., short-range-order (SRO) minerals such as ferrihydrite) have higher capacity than crystalline Fe minerals in organic matter adsorption/binding, due to a higher specific surface area (SSA) and large numbers of hydroxyl groups present on mineral surfaces (Cao et al, 2011;Chen et al, 2014b;Torn et al, 1997;Xiao et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…al., 2017). Secondary Fe-minerals (e.g., short-range-order (SRO) minerals such as ferrihydrite) have higher capacity than crystalline Fe minerals in organic matter adsorption/binding, due to a higher specific surface area (SSA) and large numbers of hydroxyl groups present on mineral surfaces (Cao et al, 2011;Chen et al, 2014b;Torn et al, 1997;Xiao et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Specifically, fertilization regimes alter microbial communities (Wen et al, 2018;Xun et al, 2016), soil pH (Guo et al, 2010), and mobilize iron (Xiao et al, 2016;Yu et al, 2017), which further affect the free radical reaction. Specifically, fertilization regimes alter microbial communities (Wen et al, 2018;Xun et al, 2016), soil pH (Guo et al, 2010), and mobilize iron (Xiao et al, 2016;Yu et al, 2017), which further affect the free radical reaction.…”
Section: Mechanisms Of Soil C Stability and Storage Through Microbimentioning
confidence: 99%
“…Interestingly, in this study, we showed that the free radical reaction could be regulated by fertilization regimes. Specifically, fertilization regimes alter microbial communities (Wen et al, 2018;Xun et al, 2016), soil pH (Guo et al, 2010), and mobilize iron (Xiao et al, 2016;Yu et al, 2017), which further affect the free radical reaction. Liu et al (2015) showed that replacing a portion of chemical fertilizers with organic manure successfully reduced greenhouse gas emissions, increased soil C stabilization and storage, and improved crop yields (Liu et al, 2015).…”
Section: Mechanisms Of Soil C Stability and Storage Through Microbimentioning
confidence: 99%
“…Solomon et al (2012) showed high complexity of the organic C functionalities and coexistence of various inorganic compounds in the thin sections from an undisturbed microaggregate of tropical Ultisol using STXM-NEXAFS [26]. They suggested that C stabilization in micro-and nano-scale regions occurred from cumulative results of physical protection and multiple chemical-binding mechanisms on external and internal surface of clay minerals [26,47]. Our results further showed the variation in C functionalities even within the single sonication-resistant aggregate isolated from the size-sorted fraction for the studied Andisol.…”
Section: 2carbon Forms Of the Organo-mineral/metal Nanocompositmentioning
confidence: 99%
“…2018, 2, 32 4 of 18 by soft X-ray scanning transmission microscopy (STXM) coupled with near edge X-ray adsorption fine structure (NEXAFS) followed by a detailed microscopic assessment of specific regions of the aggregate using a field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). STXM-NEXAFS was an ideal technique because it allowed us to characterize the spatial distribution of light elements originating from both OM and minerals as well as identifying major C forms [26,[45][46][47][48][49][50][51]. We identified OMN-rich regions within the isolated particle and discussed their possible roles in the development of hierarchical aggregate structure from a pedological perspective with a new conceptual model.…”
mentioning
confidence: 99%